1997
DOI: 10.1016/s0092-8674(00)80247-0
|View full text |Cite
|
Sign up to set email alerts
|

Sno Storm in the Nucleolus: New Roles for Myriad Small RNPs

Abstract: trimethyl guanosine (TMG) cap structure. Phylogenetic comparison of U3 snoRNAs from various species re-Department of Molecular Biophysics and vealed conserved sequence elements called boxes C Biochemistry (UGAUGA/U) and D (CUGA), which are also present in Howard Hughes Medical Institute the next vertebrate snoRNAs (U8 and U13) to be identi-Yale University fied. Boxes C and D direct binding of the abundant New Haven, Connecticut 06536nucleolar protein fibrillarin, a target of autoantibodies, and are necessary f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
193
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(195 citation statements)
references
References 14 publications
2
193
0
Order By: Relevance
“…In the 1990s, though, a major breakthrough occurred when a large number of box H/ACA guide RNAs were found to direct rRNA pseudouridylation (Balakin et al, 1996;Ganot et al, 1997;Ni et al, 1997;Smith and Steitz, 1997;Yu et al, 2005). …”
Section: Mechanisms Of Spliceosomal Snrna Pseudouridylationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 1990s, though, a major breakthrough occurred when a large number of box H/ACA guide RNAs were found to direct rRNA pseudouridylation (Balakin et al, 1996;Ganot et al, 1997;Ni et al, 1997;Smith and Steitz, 1997;Yu et al, 2005). …”
Section: Mechanisms Of Spliceosomal Snrna Pseudouridylationmentioning
confidence: 99%
“…About 15 years ago, though, several laboratories began to turn their attention to the mechanisms and functions of these modifications in spliceosomal snRNAs and rRNAs (Bachellerie et al, 1995;Cavaillé et al, 1996;KissLászló et al, 1996;Tycowski et al, 1996;Ganot et al, 1997;Ni et al, 1997;Smith and Steitz, 1997;Tycowski et al, 1998;Yu et al, 1998;Lowe and Eddy, 1999). Multiple effective assays and systems have since been developed for RNA modification research [reviewed in (Wu et al, 2011b)].…”
Section: Introductionmentioning
confidence: 99%
“…The nucleolus compartment of eukaryotic cells is devoted to the assembly of large and small ribosomal subunits (reviewed by Mélèse & Xue, 1995)+ The association of almost 80 ribosomal proteins into 60S and 40S subunits occurs concomitantly with the maturation of ribosomal RNA (rRNA) molecules+ The rRNAs have a mixed transcriptional origin+ The nucleolar RNA polymerase I transcribes a single, large rRNA precursor 35S which is processed into three mature rRNAs (18S, 5+8S and 25S)+ The fourth eukaryotic rRNA molecule (5S) is transcribed independently by RNA polymerase III+ The 5S, 5+8S and 25S rRNA species constitute the RNA molecules of mature 60S subunits whereas mature 40S subunits contain only 18S rRNA+ The maturation of the pre-rRNA 35S polymerase I transcript is largely studied in yeast and numerous small nucleolar RNAs (snoRNAs) and protein components involved in this process have been characterized (Eichler & Craig, 1994;Venema & Tollervey, 1995;Tollervey & Kiss, 1997)+ The 35S primary transcript is successively matured by both endonucleolytic and exonucleolytic cleavages that generate stable rRNA precursors whose identification by in vivo labeling or by Northern hybridization has led to the processing pattern drawn in Figure 1+ The nucleic cleavages contribute to a precise excision of both external (59 and 39 ETS) and internal transcribed spacers (ITS1 and ITS2) that interrupt the 35S rRNA sequence+ Aberrations in any of the cleavage steps result in a defective maturation that modifies the reference pattern shown in Figure 1+ In such cases, an increase or decrease in intermediate precursors is evident whereas some aberrant and sometimes deadend pre-rRNA species are detected+ This observation of altered profiles is classically used to determine at which step either a given mutation or the depletion of a cellular component will affect the rRNA maturation process+ These approaches have indeed revealed that a large number of trans-acting factors are required for the same processing step (Venema & Tollervey, 1995)+ For example, the snoRNAs U3, U14, snR30, and snR10 are all essential (or at least important in the case of snR10) for efficient cleavage at sites A 0 , A 1 , and A 2 (Tollervey, 1987;Li et al+, 1990;Hughes & Ares, 1991;Morrissey & Tollervey, 1993; see Fig+ 1B)+ The snoRNAs are believed to function as small nucleolar ribonucleoprotein (snoRNP) complexes rather than as free RNAs (Maxwell & Fournier, 1995) and some nucleolar proteins were shown to be physically associated with snoRNAs (Maxwell & Fournier, 1995;Smith & Steitz, 1997)+ Two RNP particles involved in the yeast rRNA processing are considered in this article: the abovementioned snoRNP complex (Venema & Tollervey, 1995) and the RNase MRP complex …”
Section: Introductionmentioning
confidence: 99%
“…The nucleolus is a prominent organelle in the nucleus of eukaryotic cells+ It is the site of ribosome biogenesis, which involves ribosomal RNA (rRNA) synthesis, modification and processing, and association with ribosomal proteins+ Several of these events are mediated by small nucleolar RNAs (snoRNAs)+ There are about 200 snoRNA species in the nucleolus, most of which are used to guide the modifications that occur on pre-rRNA: 29-O-ribose methylation by snoRNA members of the Box C/D family (Cavaillé et al+, 1996;Kiss-László et al+, 1996Maden, 1996;Nicoloso et al+, 1996;Tollervey, 1996;Tycowski et al+, 1996;Maden & Hughes, 1997;Smith & Steitz, 1997), and pseudouridine formation by snoRNA members of the Box H/ACA family (Ganot et al+, 1997;Ni et al+, 1997;Smith & Steitz, 1997)+ The function of these modifications in rRNA is not yet understood, and the snoRNAs utilized for rRNA modifications are dispensable+ In contrast, there are a handful of snoRNAs that are essential for viability of the cell, and are required for rRNA processing events that remove the external transcribed spacers and internal transcribed spacers from the rRNA precursor (summarized in Gerbi, 1995;Maxwell & Fournier, 1995;Sollner-Webb et al+, 1995;Venema & Tollervey, 1995)+ These include U3 (Kass et al+, 1990;Savino & Gerbi, 1990;Hughes & Ares, 1991;Hughes, 1996), U8 (Peculis & Steitz, 1993, U14 (Jarmolowski et al+, 1990;Li et al+, 1990;Li & Fournier, 1992;Liang & Fournier, 1995;Dunbar & Baserga, 1998;Lange et al+, 1998), U22 (Tycowski et al+, 1994), and E1 (ϭU17), E2, and E3 (Mishra & Elicieri, 1997)+ U3 and U14 are used for rRNA processing both in metazoa and in yeast, but the other snoRNAs listed above have only been identified in metazoa+ There are some additional snoRNAs that are essential for rRNA processing that have only been found in yeast+ Of all the snoRNAs that have been identified, U8...…”
Section: Introductionmentioning
confidence: 99%